Influência do sistema de produção no semiárido brasileiro sobre o perfil de ácidos graxos, voláteis e sensorial do leite e queijo caprino - Silva, Amanda Marília da (2017)
Caprine livestock is among the main economic activities in semi-arid region of Northeastern Brazil which is characterized by low rain rates and a dry weather, where caatinga biome represents the most important feed source for caprine herds. In this study, we evaluated the fatty acids and volatile compounds profiles as well as the sensorial properties of milk and cheese from caprines kept and raised under different systems in semi-arid Brazil, confined space and open pastures. An optimization of the extraction conditions for the volatile compounds in caprine milk was made by using Response Surface Methodology. From this statistical tool we could identify the best conditions to maximize the number of volatile compounds extracted, corresponding them to 15 minutes for equilibrium time, 30 minutes for extraction time and 45 °C for extraction temperature. Using these conditions, 19 different volatile compounds were identified. Amongst these compounds, octanoic acid (caprylic acid) and decanoic acid (capric acid) can be highlighted with having larger relative areas, and they are volatile fatty acids correlated to the characteristic flavor presented in caprine milk. The dairy caprines (Saanen and American Alpine) used were divided into two groups: Caprines fed in open pasture plus concentrate supplementation (OF) and those fed in confined space (CS) with hay and concentrate. Milk and cheese from animals fed in OF presented higher content of fatty acids for oleic acid (C18:1c9), stearic acid (C18:0), polyunsaturated (PUFA) and monounsaturated (MUFA), including C16:1c7 C16:1c9 e C17:1c9, isomers cis and trans of C18:1, linoleic acid (C18:2n6), linolenic acid (C18:3n3), arachidonic acid (C20:4n6), desired fatty acids (DFA) and higher PUFA/SFA and MUFA/SFA rates. Several volatile compounds found in milk and cheese from OF were not present in CS, such as the terpene compounds α-terpineol e β-caryophyllene. The milk from OS was described for having a more intense herbal flavor whereas the milk from CS was more intense in butter flavor and taste and showed a higher residual aftertaste. Regarding to the sensorial properties of the cheese, no differences were found between the two different systems, however, the overall acceptability was higher for milk and cheese from animals feed in OF. Our results suggest that raising caprines in open field can be considered the best production system to be used in semi-arid region of Northeastern Brazil as it valorizes the use of the native pasture found in Caatinga to feed caprine herds, being an interesting economic alternative for the local farmers.